2^(-1)*27^(2/3)=9/2
2006-11-02 09:52:15
·
answer #1
·
answered by Pascal 7
·
0⤊
0⤋
To do this, start by considering 27^(2/3). Now, when you have an expression of the form x^(1/n), where n is a positive integer, this means the same thing as "the nth root of x".
So, 27^(2/3) = (27^(1/3))^2, by rules of indices. However, note that 27^(1/3) means the cube root of 27. Now, 3x3x3=9x3=27. Thus 3 is the cube root of 27.
Now, substituting this back into the equation, we get:
2^(-1)x(3^2)
2^(-1)x9
Now, if you have an expression of the form x^(-n), where n is a positive integer, then this is the same as (1/x)^n. So
2^(-1)x9=9/2
2006-11-02 19:15:56
·
answer #2
·
answered by friendly_220_284 2
·
0⤊
0⤋
The tricky part is 27(to the power 2/3).
27 to 1/3 is 3.
27 to 2/3 is 3 x 3 of 27 = 9.
27 to 3/3 is 27 to the power of one = 27
So without a calulator the answer = 2 x 9 = 18
2006-11-02 09:58:55
·
answer #3
·
answered by Ta 3
·
0⤊
1⤋
4.5
2 to the power -1 = 1/2
27 to the power 2/3 = (cube root of 27)^2 = 3^2 = 9
1/2 Ã 9 = 9/2 or 4.5
2006-11-02 09:54:10
·
answer #4
·
answered by THJE 3
·
0⤊
0⤋
2^-1 * 27^2/3 = 1/2 * cube root of 27^2 = 1/2 * 9 = 9/2 = 4 1/2
2006-11-02 09:52:04
·
answer #5
·
answered by disposable_hero_too 6
·
0⤊
0⤋
to the power -1 means 1 over
= 1/2 x 27^2/3
to the power 2/3 is cube root and square it
= 1/2 x (cube root)27squared
= 4.5
= 9/2
2006-11-03 06:29:29
·
answer #6
·
answered by Jen 2
·
0⤊
0⤋
2^(-1) x 27^(2/3)
= (1/2) x Cube root of (27)^2
= (1/2) x 3^2
= (1/2) x 9
= 4.5 or 4 1/2
2006-11-02 10:57:10
·
answer #7
·
answered by Kemmy 6
·
0⤊
0⤋
9/2
2006-11-02 09:54:17
·
answer #8
·
answered by buffsteakhouse 1
·
0⤊
0⤋
2^-1=1/2
27^2/3=(quebed root of 27)^2
so its 1/2 x 3^2
=1/2 x 9
=4.5
2006-11-03 21:17:43
·
answer #9
·
answered by Wojciech S 2
·
0⤊
0⤋
{(2^(-1)*(27)^(2/3)} = (1/2)*{27^2}^(1/3)
={cube root(27*27)}/2
={3*3}/2=9/2
i hope that this helps
2006-11-02 20:31:26
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋